The Dalai Lama and Religious Diversity - de Cea, Abraham Vélez (Interreligious Studies and Intercultural Theology, 2020)
This article challenges exclusivist interpretations of the Buddha, and proposes alternative readings of early Buddhist texts that allow for the existence of the ultimate goal of the spiritual life outside Buddhism. The article clarifies the differences between exclusivist and non-exclusivist exegesis of the Buddha and suggests that exclusivist readings of his thought are a later scholastic development in the history of Buddhism. The main thesis of the article is that the Buddha cannot be considered an exclusivist because he did not understand the Dhamma and selfenlightened beings (paccekabuddhas) in sectarian terms as being the monopoly of any school. What the Buddha excludes from being paths to the final goal of the spiritual life are specific teachings incompatible with the Dhamma and the Noble Eightfold Path. This exclusion of specific teachings rather than of entire schools entails “specific exclusivism,” which is different from holding a sectarian “exclusivist view” of all non-Buddhists traditions anywhere and at any time.